Advanced organic chemistry : - March, Jerry (John Wiley, 1992)
The book contains 19 chapters which are concerned with organic reactions and their mechanisms. It describes the structure of organic compounds, including chemical bonding and stereochemistry; reviews general reaction mechanisms, including ordinary reactions and photochemical reactions. It also includes a survey of reactions, arranged by reaction type and by which bonds are broken and formed